A variety of Helicobacter pylori strains colonize the stomach of non-bleeding Egyptian patients with upper gastrointestinal disorders - Eldeen, Loaa A. Tag (2021)
BLAST results of H. pylori 16s rRNA gene sequences showed identity between Egyptian H. pylori isolates and four H. pylori strain subpopulations: hspSAfrica, hspEAsia, hpEurope, hspWAfrica. The frequency of H. pylori isolates that showed identity to hspEAsia subpopulation was significantly higher in Ulcerative lesions. H. pylori isolates from ulcerative and neoplasm specimens illustrate base substitutions in 16s rRNA gene variable 9 region compared to the consensus sequence of H. pylori 43504 16s rRNA.